Endovascular Repair of Aortic Arch Aneurysm with Surgeon-Modified Fenestrated Stent Graft - Manunga, Jesse (AORTA, 2018)
The authors describe a technique of treating patients with aortic arch aneurysm using surgeon-modified fenestrated stent graft (SMFSG). The technique is demonstrated in a 80-year-old patient whose aneurysm was successfully excluded with a SMFSG using Cook Alpha thoracic stent graft. The device was deployed, removed from its delivery system, and a fenestration created before being mounted back on the delivery system and constrained. It was transitioned through a series of sheaths before being introduced into its original sheath. The device was implanted via a common femoral artery access site; fenestration cannulated from the left brachial artery and bridged with a stent graft.
Keywords: aortic arch aneurysm; endovascular repair; fenestrated stent graft; surgeon-modified fenestrated graft